2009
DOI: 10.1002/ppap.200930705
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Aluminum Using a Combined Technique of Barrel Nitriding and Plasma Nitriding

Abstract: In this study, a new nitriding process is proposed to produce the aluminum nitride on the aluminum surface. A process of combined barrel and plasma nitriding techniques was used. By using the barrel nitriding process, an aluminum nitride layer with high thickness can be formed within a matter of hours, and the surface hardness can be improved by using the plasma nitriding. It is suggested that a combined technique of the barrel nitriding and the plasma nitriding is one of the most promising surface treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A barrel tank was used for surface nitriding of aluminum substrates. Details of the nitriding system have been reported previously 6,7) . The barrel tank used in this study was octagonal, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A barrel tank was used for surface nitriding of aluminum substrates. Details of the nitriding system have been reported previously 6,7) . The barrel tank used in this study was octagonal, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The nitrogen then diffuses onto the surface of the material creating nitride layer [2]. Nitriding an aluminum surface is very hard due to the thin oxide layer existing on the surface which keeps the dispersion of nitrogen into the aluminum substrate making it a slowly process [7]. Gas pressure did not have any significant effect to the thickness of layer as thickness remains constant if the gas pressure increases [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gas pressure did not have any significant effect to the thickness of layer as thickness remains constant if the gas pressure increases [8]. Aluminum has no diffusion zone like other metal [7]. Aluminum surface will change from metallic silver to dark gray or shiny black after nitriding due to the formation of aluminum nitride layer on the surface [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Okumiya et al Combined barrel nitriding and plasma nitriding, a bilayer aluminum nitride on aluminum can be produced [11]. Khan et al studied nitriding of aluminum alloy in nitrogen and nitrogen-helium mixture using a 100 Hz-pulsed DC glow discharge.…”
Section: Introductionmentioning
confidence: 99%